Models for cost-offset community supported agriculture (CO-CSA) programs - Sitaker, Marilyn; McCall, Mackenzie; Wang, Weiwei; Vaccaro, Mia; Kolodinsky, Jane; Ammerman, Alice; Jilcott Pitts, Stephanie; Hanson, Karla; Smith, Diane; Seguin-Fowler, Rebecca (Journal of Agriculture, Food Systems, and Community Development, 2021)
Cost-offset community supported agriculture (CO-CSA) appears to be a promising way to increase low-income households’ access and intake of fresh produce, while also helping CSA farms expand their farm business. Yet single farms operating CO-CSAs may struggle to balance the demands of farming with CO-CSA program administration, funding, and recruitment. To address these challenges, CO-CSA programs operated by nonprofits have emerged, equipped with dedicated infrastructure, resources, and staffing. This study aims to describe organizational models and best practices of nonprofit CO-CSA programs, using a qualitative approach. We conducted interviews with five well-established nonprofit CO-CSA programs in the U.S. Administration of these five nonprofit CO-CSAs took several forms: (1) providing direct subsidies to individual CO-CSA member farms; (2) functioning themselves as an aggregator, packer, and distributor of regional produce; and (3) sourcing from an in-house farm incubator or food hub, then packing and coordinating delivery to pick-up sites. Nonprofit CO-CSA funding strategies included grants from federal and local government sources, private donations, fundraising, and grants. Marketing efforts occurred via social media, community events, and word of mouth. Both fundraising and recruitment were greatly facilitated by relationships with community partners. Having dedicated staff, as well as a community that values local agriculture and social justice, were identified as success factors. This descriptive, qualitative study systematically compares the attributes of five nonprofit CO-CSA programs. Future research should focus on identifying the cost-effectiveness of nonprofit CO-CSAs, compare the relative merits of single-farm and nonprofit CO-CSAs, and quantify the economic benefit of CO-CSA programs for farmers and local communities.